Impact of Complete Versus Incomplete Circumferential Lines Around the Pulmonary Veins During Catheter Ablation of Paroxysmal Atrial Fibrillation: Results From the Gap-Atrial Fibrillation–German Atrial Fibrillation Competence Network 1 Trial. (January 2016) - Kuck, Karl-Heinz; Hoffmann, Boris A.; Ernst, Sabine; Wegscheider, Karl; Treszl, Andras; Metzner, Andreas; Eckardt, Lars; Lewalter, Thorsten; Breithardt, Günter; Willems, Stephan
Abstract : Background—: Ablation of atrial fibrillation (AF) is an established treatment option for symptomatic patients. It is not known whether complete pulmonary vein isolation (PVI) is superior to incomplete PVI with regard to the patients' clinical outcome. Methods and Results—: Patients with drug-refractory, symptomatic paroxysmal AF were randomly assigned to either incomplete (group A) or complete PVI (group B). In group A, a persistent gap was intentionally left within the circumferential ablation line, whereas in group B, complete PVI without any gaps was intended. At 3 months, all patients underwent invasive reevaluation to assess the rate of persistent PVI. Clinical follow-up was based on daily 30-s transtelephonic ECG transmissions. Primary study end point was the time to first recurrence of (symptomatic or asymptomatic) AF. A total of 233 patients were enrolled (116 in group A and 117 in group B). AF recurrence within 3 months was observed in a total of 161 patients (136 [84.5%] with symptomatic and 25 [15.5%] with asymptomatic AF); AF recurred in 62.2% of group B patients and 79.2% of group A patients ( P <0.001), for a difference in favor of complete PVI of 17.1% (95% confidence interval, 5.3%–28.9%). Invasive restudy in 103 group A patients and 93 group B patients revealed conduction gaps in 92 (89.3%) and 65 (69.9%) patients, respectively. Conclusions—: This study proves the superiority of complete PVI over incomplete PVI with respect to AF recurrence within 3 months. However, the rate of electric reconduction 3 months after PVI is high in patients with initially isolated PVs. Clinical Trial Registration—: URL:http://clinicaltrials.gov ; Unique identifier: NCT00293943.